When emergency medicine becomes a staple diet: Evidence from Indian banking crisis - Mannil, Nithin; Nishesh, Naman; Tantri, Prasanna (Journal of Banking & Finance, 2024)
We investigate the role of regulatory forbearance in causing a banking crisis. To mitigate the expected spillover effects of the global financial crisis, the Indian banking regulator allowed banks to restructure loans without creating provisions. The forbearance continued beyond the crisis due to political economy-related considerations. Using heterogeneity in the application of the policy, we find that healthy banks that benefited from forbearance became undercapitalized due to the non-recovery of unhealthy borrowers whose accounts were restructured. The undercapitalization led to distortionary lending practices; some distortions took the form of a quid pro quo between the government and the undercapitalized banks.